Longer-Term Psychiatric Inpatient Care for Adolescents A Multidisciplinary Treatment Approach - Hazell, Philip (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
This open access book describes the theoretical underpinnings and operational aspects of delivering longer-term inpatient psychiatric care to adolescents experiencing severe, unremitting mental illness. The authorship is drawn from the multidisciplinary team that supports the Walker Adolescent Unit, located in Sydney, Australia. The book begins with an account of the planning and development of the unit, an examination of the physical environment, and the adaptations that have been made to ensure its functionality. There follows a consideration of the therapeutic milieu. The book describes clinical processes such as admission and discharge planning, formulation and case review. There is information about the specific roles of professionals and the therapies that they provide. The book describes the steps taken to maintain and enhance the physical wellbeing of patients. There are chapters dedicated to governance, and to training and education. The final chapter describes how the unit responded to challenges created by the COVID-19 pandemic. Philip Hazell is Conjoint Professor of Child and Adolescent Psychiatry with The University of Sydney and a consultant psychiatrist with the Sydney Local Health District. In former roles as director of child and adolescent mental health services he was responsible for the commissioning of two psychiatric inpatient units for adolescents.